APPENDICEAL CANCER INVADING THE ABDOMINAL WALL: A CASE REPORT AND LAPAROSCOPIC SURGICAL MANAGEMENT - Duy Đạt, Đỗ; Văn Hưng, Nguyễn; Quang Nhật, Phạm; Lê Bảo, Hồ (Journal of Health and Aging, 2025)
Appendiceal cancer is a rare condition, often diagnosed late due to nonspecific symptoms. We report a case of appendiceal cancer invading the abdominal wall to evaluate the effectiveness of laparoscopic surgery and a multimodal treatment strategy. A 60-year-old male patient was admitted with persistent right iliac fossa pain for 2 months and a 3kg weight loss. Imaging confirmed an 6x8cm appendiceal tumor invading the abdominal wall and cecum, causing partial bowel obstruction. The patient underwent laparoscopic right hemicolectomy with D2 lymphadenectomy. Pathology confirmed moderately differentiated adenocarcinoma with metastases to 12/17 lymph nodes and peritoneal fluid (stage IVB). Postoperative recovery was uneventful, and the patient was discharged on day 7 with adjuvant chemotherapy scheduled. After 3 weeks of follow-up, the patient remained stable. This case highlights the importance of early diagnosis and radical surgery, combined with adjuvant therapy, in improving outcomes for patients with advanced-stage appendiceal cancer.
Keywords: Appendiceal cancer; laparoscopic surgery; peritoneal metastasis; D2 lymphadenectomy; stage IVB